The role of product promotion and product packaging in generating consumer buying interest at Tiara Sari Cake Shop - Sutopo Sutopo; Sudianto Sudianto; Anang Martoyo (SINTESA, 2022)
Promotion is the key to success in business. When the promotion that is run is right, usually customers will be loyal to continue to buy. Product packaging has a strong influence on consumer purchase intentions, especially at the point of sale. Packaging serves as a means of promotion because packaging that can protect and facilitate the use of the product adds value to the sale and promotion of the product. Packaging is able to add value to consumers if it is in accordance with the function of the packaging itself, such as a place that fits the load capacity of a product and also becomes a differentiating identity from other products, so that consumers are sure to buy. The purpose of this study was to find out how the role of product promotion, product packaging, consumer buying interest at the Tiara Sari cake shop. The method uses a qualitative research approach and literature study (Library Research) which is useful for obtaining a series of descriptions of the factors that influence the results of the variables studied. This research step uses data collection methods from online journals literature sourced from Google Schooler. The results of product promotion research affect consumers in generating consumer buying interest, packaging has a negative impact on the variable of consumer buying interest, which means that the lower the quality of the packaging, the lower the consumer's interest in buying a product. The conclusion of the role of product promotion in generating consumer buying interest at the Tiara Sari cake shop can be seen specifically for respondents with low packaging perceptions, high promotional perceptions increase purchase intentions more than low promotional perceptions, if the product quality is good, although not there is a product promotion, consumers can still buy the product so that the better the quality of the product it produces will provide an opportunity for consumers to make purchasing decisions. In addition, the role of product packaging in generating consumer buying interest at the Tiara Sari cake shop is already functioning properly, the packaging has an influence (gives a negative impact) on consumer buying interest, which means that the lower the quality of product packaging, the lower the consumer interest in buying a product. Product packaging has a great influence on buyers when making purchasing decisions, product packaging moderated by promotions generates consumer buying interest. Although good packaging does not guarantee good product quality.